DEVELOPING CHART OF ACCOUNT BASED ON FINANCIAL ACCOUNTING STANDARD - Fadhla Khanifa; sukirno sukirno (Jurnal Pendidikan Akuntansi Indonesia, 2017)
The research aims to know the developing process of Chart of Account, to know its feasibility, and to know the students of SMAN 1 Kalasan class XII IPS opinion about the utilization of Chart of Account as a learning media. The type of research is Research and Development with following the ADDIE research model. Media was tested in 27 students of SMAN 1 Kalasan class XII IPS 1. The result of this research presented that the media is feasible to use, and proven by validation from material expert got score 4,27 with “Totally Feasible” category, from a media expert got score 4,33 with “Totally Feasible” category, and from accounting learning practitioner got score 4,81 with “Totally Feasible” category. Responses from students of this media were interesting, practical and really helpful in learning the accounting subject.Keyword: Mobile Learning, Chart of Account, Android